Lipid Disturbances in Psoriasis: An Update - Aldona Pietrzak; Anna Michalak-Stoma; Grażyna Chodorowska; Jacek C. Szepietowski (Hindawi Limited, 2010)
Psoriasis is a common disease with the population prevalence ranging from 2% to 3%. Its prevalence in the population is affected by genetic, environmental, viral, infectious, immunological, biochemical, endocrinological, and psychological factors, as well as alcohol and drug abuse. In the recent years, psoriasis has been recognised as a systemic disease associated with numerous multiorgan abnormalities and complications. Dyslipidemia is one of comorbidities in psoriatic patients. Lipid metabolism studies in psoriasis have been started at the beginning of the 20th century and are concentrated on skin surface lipids, stratum corneum lipids and epidermal phospholipids, serum lipids, dermal low-density lipoproteins in the psoriatic skin, lipid metabolism, oxidative stress and correlations between inflammatory parameters, lipid parameters and clinical symptoms of the disease. On the basis of the literature data, psoriasis can be described as an immunometabolic disease.